Factors related to the expression of emotions by early-stage breast cancer patients. Issue 10 (October 2019) - Del Piccolo, Lidia; Mazzi, Maria Angela; Mascanzoni, Andrea; Lonardi, Miriam; De Felice, Mariangela; Danzi, Olivia Purnima; Buizza, Chiara; Ghilardi, Alberto; Bottacini, Alessandro; Goss, Claudia
Highlights: Patients expressed their emotions mainly as cues. Therefore, not in explicit way. Emotional expressions increased with oncologists' diagnosis of anxiety. Emotional expressions increased with patient-centred approach. Emotional issues were reduced by the adoption of a more structured consultation. Both organizational and interaction aspects are relevant on emotional expression.. Abstract: Objective: (1) To report the number and type of emotional expressions (cues/concerns) raised by breast cancer patients; (2) to identify the influence of setting, patient characteristics, and doctor-patient interaction on emotional expression. Methods: 308 Italian-speaking female patients were recruited at their first breast cancer consultation. The visits were audio-recorded and analysed for number and type of emotional expressions (VR-CoDES). Oncologists' interaction skills were rated by the VR-COPE. Socio-demographic, clinical and personality variables were gathered before the consultation. Clinical variables and oncologists' evaluations of the patient were collected after. Results: Breast cancer patients raised emotional issues mainly as cues. The setting (centre where the consultations took place), the oncologist's attribution of anxiety, regardless of anxiety test screening (STAI-X1) score before the consultation, and the oncologist's ability to pick up on patient's worries, handle emotional needs or understand psychosocial condition were all positively related with the number of emotional expressions. More tightly structured consultations had fewer emotional expressions. Conclusion: Both contextual and interactional aspects have an impact on patient emotional expressions. Practice implications: Oncologists need to be trained to manage both the content and the process of medical consultation. Work organization of the consultation setting needs to be taken into account.